1997
DOI: 10.1557/proc-469-101
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of Czochralski Silicon from P-Type to N-Type by Hydrogen Plasma Enhanced Thermal Donor Formation

Abstract: Our experiments show a hydrogen plasma assisted creation of p-n junctions in p-type Cz silicon due to a hydrogen enhanced thermal donor (TD) formation at temperatures ≤450 °C. Applying DC or HF plasma treatments a conversion of p-type into n-type Cz silicon by TD formation occurs. One can distinguish one step processes (p-n junction formation appears just after the plasma exposure) and two step processes (p-n junction formation requires subsequent post hydrogenation annealing). The samples are studied by depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, numerous studies have demonstrated the thermal stability of different kinds of STDs up to temperatures well above 450°C; [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][43][44][45][46][47] thus, we discard this possibility here. Passivation corresponds with a further reaction, for example given by H + HX ⇔ H 2 X, if the STDH center ͑HX͒ is a single donor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, numerous studies have demonstrated the thermal stability of different kinds of STDs up to temperatures well above 450°C; [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][43][44][45][46][47] thus, we discard this possibility here. Passivation corresponds with a further reaction, for example given by H + HX ⇔ H 2 X, if the STDH center ͑HX͒ is a single donor.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenation-induced donor formation in p-type silicon.-In p-type hydrogenated silicon, the introduction of STDs yields a type of conversion, whereby the p-n junction moves along with the hydrogen diffusion front. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Consequently, the junction profile is not abrupt but rather linear as illustrated by Fig. 1, which should be taken into account when deriving carrier concentration profiles from C-V and OTD concentrations from DLTS measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In p-type hydrogenated silicon, the introduction of STDs yields a type conversion, whereby the p-n junction moves along with the hydrogen diffusion front [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Consequently, the junction profile is not abrupt but rather linear as illustrated by Fig.…”
Section: Hydrogenation-induced Donor Formation In P-type Siliconmentioning
confidence: 99%
“…At the same time, hydrogen-related Shallow TDs (STDHs) have also been observed [7][8][9][10][11][12][13], with ionization energies in the range 35-40 meV and infrared absorption peaks in the sub 300 cm -1 range typically. These centers can be exploited for the low-temperature formation of deep p-n junctions in p-type Cz silicon [14][15][16][17][18][19][20][21][22][23][24]. An example is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%